2012
DOI: 10.1021/om201288p
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Grubbs Catalysts with Excess Methoxide: Formation of Novel Methoxyhydride Complexes

Abstract: On exposure to NaOMe (≥3 equiv) in CH2Cl2–MeOH at 23 °C, the first-generation Grubbs catalyst RuCl2(PCy3)2(CHPh) (1a) is immediately transformed into the six-coordinate methoxyhydride complexes RuH(OMe)(CO)2(PCy3)2 (4a) and RuH(OMe)(CO)(H2)(PCy3)2 (5a). Complex 5a can be recycled into 4a under conditions conducive to removal of H2. The second-generation catalyst RuCl2(IMes)(PCy3)(CHPh) (1b; IMes = N,N′-bis(mesityl)imidazol-2-ylidene) reacts more slowly, requiring several hours even at 20 equiv of NaOMe, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 62 publications
1
26
0
1
Order By: Relevance
“…16 Most commonly cited in recent reports is the potential involvement of two hydride complexes ([Ru 2 (μ‐C)Cl 3 (H)(H 2 IMes) 2 ] ( Ru‐1 ) and [RuCl(CO)H(H 2 IMes)(PCy 3 )] ( Ru‐2 )], accessible by decomposition of GII (Scheme ) 17. Dinuclear Ru‐1 was shown by Hong and Grubbs to form on thermolysis of the resting‐state methylidene complex (albeit slowly),16 whereas several reports describe routes to hydridocarbonyl complexes of type Ru‐2 from GII 1820. Notably, Percy and co‐workers observed Ru‐2 during ring‐closing metathesis of 1,7‐octadiene by GII ,21 and the Grubbs and Mol groups found that closely related carbonyl complexes form on exposure of the Grubbs catalysts to oxygen 17f,h.…”
Section: Methodsmentioning
confidence: 99%
“…16 Most commonly cited in recent reports is the potential involvement of two hydride complexes ([Ru 2 (μ‐C)Cl 3 (H)(H 2 IMes) 2 ] ( Ru‐1 ) and [RuCl(CO)H(H 2 IMes)(PCy 3 )] ( Ru‐2 )], accessible by decomposition of GII (Scheme ) 17. Dinuclear Ru‐1 was shown by Hong and Grubbs to form on thermolysis of the resting‐state methylidene complex (albeit slowly),16 whereas several reports describe routes to hydridocarbonyl complexes of type Ru‐2 from GII 1820. Notably, Percy and co‐workers observed Ru‐2 during ring‐closing metathesis of 1,7‐octadiene by GII ,21 and the Grubbs and Mol groups found that closely related carbonyl complexes form on exposure of the Grubbs catalysts to oxygen 17f,h.…”
Section: Methodsmentioning
confidence: 99%
“…18 Reactions were run utilizing the standard conditions described above. Of the three catalysts, 9 gave the best results, providing the homodimerization products in high conversions (>95% and 77% for 13 and 14 , respectively) with >95% Z- selectivity for both substrates.…”
mentioning
confidence: 99%
“…10-Methyl undecenoate ( 32 , Table 3) was selected because the ester functionality is far removed from the double bond, while 4-pentenol ( 34 , Table 4) has been linked to decomposition pathways of prior generations of Ru-metathesis catalysts. 27 Furthermore, pronounced Z -content degradation has been observed in the homodimerization of 4-pentenol with previous Z -selective metathesis catalysts 7 and 8 . Metathesis reactions were executed utilizing the standard conditions described above.…”
Section: Resultsmentioning
confidence: 79%